Students’ Suicide in Ptolemaic Alexandria? - Pozdnev, Michael (Hyperboreus, 2018)
The romantic story of the forceful lectures of the Cyrenaic Hegesias held responsible for suicides among his audience in Alexandria and consequently weaned off lecturing by Ptolemy Soter, although well-rooted both in derivative tradition, translation and commentary, hangs on a single locus in Cicero’s Tusc. 1. 83 and appears to have been spun out of thin air. This piece aims at unwinding this story all the way through the fully derivative testimonies of Valerius Maximus and Plutarch, both serving their own ends, down to its source text which plainly is not about lecturing, but the power of the written word, to which Cicero, while disclaiming responsibility for the evidence, drew concern Ptolemy voiced about the potentially harmful theory.